Juridical Analysis of the Use of a Power of Attorney to Sell Made Before a Notary that Gives Rise to the Criminal Act of Money Laundering (Case Study of Decision Number 248/Pid.B/2022/PN JKT.Brt) - Alinda Julietha Adnan; Ali Abdullah (Dinasti Research, 2026)
This research is motivated by the misuse of a power of attorney to sell made before a notary without the presence and consent of the legally entitled party, whereby the deed was subsequently used as the basis for the unlawful transfer of land rights. This issue is important to examine because notarial deeds and deeds made by Land Deed Officials possess strong evidentiary value, yet in practice they may be misused to create the appearance of legality for transactions that are in fact contrary to law. This study aims to analyze the legal standing of a power of attorney to sell in relation to a deed made before a notary without the presence of the parties, as well as to analyze the use of such power of attorney that may give rise to the criminal act of money laundering. This research employs normative legal research using statutory and case approaches. The object of this study is the Decision of the West Jakarta District Court Number 248/Pid.B/2022/PN Jkt.Brt, examined through primary, secondary, and tertiary legal materials. The data were obtained through library research and analyzed qualitatively by connecting legal provisions, doctrines, and legal facts contained in the court decision. The results of the study indicate that a power of attorney to sell made without the presence of the parties does not fulfill the formal requirements of an authentic deed, as the notary is unable to verify the identity, intention, and consent of the grantor. Such a deed may lose its authentic evidentiary force and may be challenged as the basis for the transfer of land rights. Furthermore, the unlawful use of a power of attorney to sell may serve as a means to transfer, conceal, or disguise the origin of assets derived from criminal acts, particularly when certificates that have been transferred into another name are subsequently pledged as collateral, sold, or used to obtain economic benefit. These findings affirm that violations of deed-making procedures may affect the validity of a transaction and give rise to criminal liability.